Flipchart Media Education in Increasing Knowledge and Attitudes of Hypertension Patients - Basrudin, Basrudin; Sitti Nur Djannah, Raden; Handayani, Lina (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Hypertension is a major problem among the elderly characterized by a high and increasing prevalence. However, the knowledge and attitudes of the elderly regarding hypertension are still relatively low. Flipchart education for elderly hypertension patients is one of the efforts to improve the knowledge and attitude of the elderly, as well as increase patient satisfaction with health services. This study aims to determine the effectiveness and impact of flipchart education on the knowledge and attitudes of hypertension patients in the elderly. This study is an experimental study using a quasi-experimental approach. The study population consisted of 136 elderly people diagnosed with hypertension. Sampling was carried out using non-probability sampling method with convenience sampling, namely selecting samples based on convenience and practicality. Data analysis was performed using bivariate analysis with paired sample T-test using SPSS Version 25 software. The results showed that before receiving flipchart education, the elderly had an average knowledge score of 11.43, which increased to 14.46 after the intervention. Similarly, the average attitude score increased from 45.82 before education to 64.70. The paired correlation results showed a significant p-value of 0.000 (<0.05). Education with flipchart media is effective and has a significant effect on increasing knowledge and attitudes in elderly people with hypertension.